Non-Invasive Fibrosis Assessment Predicts Sustained Virological Response to Telaprevir with Pegylated Interferon and Ribavirin for Chronic Hepatitis C. Issue 2 (February 2015) - Ogawa, Eiichi; Furusyo, Norihiro; Shimizu, Motohiro; Ihara, Takeshi; Hayashi, Takeo; Harada, Yuji; Toyoda, Kazuhiro; Murata, Masayuki; Hayashi, Jun
Background: Liver fibrosis remains one of the most important predictors of sustained virological response (SVR) in this era of direct-acting antiviral treatment of chronic hepatitis C. We compare non-invasive fibrosis assessment with liver biopsy (METAVIR) in terms of their ability to predict SVR by telaprevir (TVR)-based triple therapy. Methods: This prospective study consisted of 108 patients with chronic HCV genotype 1 infection who received TVR in combination with pegylated interferon (PEG-IFN)-α2b and ribavirin (RBV). Non-invasive fibrosis data included transient elastography (FibroScan), FIB-4 index and aspartate aminotransferase to platelet ratio index (APRI). Results: SVR was achieved by 84.3% of the patients by intention-to-treat analysis. In contrast to the high SVR rates for treatment-naive patients (87.1%, 27 of 31) and patients who previously relapsed (97.9%, 46 of 47), the SVR rate of prior partial/null responders was significantly lower (60.0%, 18 of 30). The impact of fibrosis on SVR was greater for prior partial/null responders, and fibrosis data, including both METAVIR score and non-invasive fibrosis assessments, were useful for predicting SVR. The METAVIR score (area under the receiver operating characteristic curve [AUROC] 0.91, cutoff ≤F2), FibroScan values (AUROC 0.99, cutoff ≤10.0 kPa), FIB-4 index (AUROC 0.91, cutoff ≤3.5) and APRI (AUROC 0.91, cutoff ≤0.80) were shown to have equal, excellent predictive power. Conclusions: An alternative to METAVIR score by liver biopsy, non-invasive fibrosis assessments are useful options for predicting SVR by prior partial or null responders in TVR-based triple therapy.